Exact Diagonalization Study of Double Quantum Dot System in Zero-bandwidth Limit - ., Haroon; Ahsan, M. A.H. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
Using exact diagonalization, we study double quantum dot system with one of the dots attached to the ideal leads acting as source and drain in T-shaped geometry. The leads are incorporated in zero-bandwidth limit by replacing their band structures with one level coinciding with Fermi levels in the respective leads. For the half-filled case, the spin-spin correlation for the dots are calculated numerically at zero as well as finite temperatures. At zero temperature, an antiferromagnetic correlation between the dots is observed for finite values of interdot tunneling matrix-element. The antiferromagnetic correlation between the dots changes  remarkably for large values of ondot Coulomb interaction both at zero as well as finite temperatures. The spin-spin correlation between the dots is significantly reduced even for small values of the inderdot Coulomb interaction compared to the ondot Coulomb interaction. At a small value of temperature, the spin-spin correlation between the dots exhibits a (negative) maximum due to contributions coming from thermal excitations to low-lying states.